2021
DOI: 10.1155/2021/8821318
|View full text |Cite
|
Sign up to set email alerts
|

Both Chloroquine and Lopinavir/Ritonavir Are Ineffective for COVID-19 Treatment and Combined Worsen the Pathology: A Single-Center Experience with Severely Ill Patients

Abstract: The off-label use of antiviral and antimalarial drugs has been considered by many researchers as a fast and relatively safe alternative to provide therapeutic options to treat COVID-19, but the assessment of such drug-specific effectiveness in this regard is far from complete. Especially, the current body of knowledge about COVID-19 therapeutics needs more data regarding drug effectiveness and safety in the severely ill patients with comorbidities. In the present article, we retrospectively analyze data from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…The risk of bias in observational studies was evaluated using ROBINS-I (see Figure 2 B & Supplementary Table 12 ). Eighteen studies (43%) [ 95 , 98 , 101 , 109 , 115 , 116 , 119 , 120 , 122 , 123 , 125–127 , 129–134 ] were rated as having a critical risk of bias, while another 18 studies (43%) [ 92–94 , 97 , 99 , 102–105 , 107 , 110–114 , 117 , 118 , 121 ] were rated as having a serious risk of bias. In general, studies were rated as having a serious or critical risk of bias due to confounding factors, poor descriptions of the regimen/interventions used, inadequate descriptions of treatment deviations and compliance and a lack of information in regards to a priori developed analysis plans and study protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias in observational studies was evaluated using ROBINS-I (see Figure 2 B & Supplementary Table 12 ). Eighteen studies (43%) [ 95 , 98 , 101 , 109 , 115 , 116 , 119 , 120 , 122 , 123 , 125–127 , 129–134 ] were rated as having a critical risk of bias, while another 18 studies (43%) [ 92–94 , 97 , 99 , 102–105 , 107 , 110–114 , 117 , 118 , 121 ] were rated as having a serious risk of bias. In general, studies were rated as having a serious or critical risk of bias due to confounding factors, poor descriptions of the regimen/interventions used, inadequate descriptions of treatment deviations and compliance and a lack of information in regards to a priori developed analysis plans and study protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies [ 31 , 85 , 86 , 93–95 , 97 , 98 , 108 , 110 , 112 , 113 , 116 , 118 , 127 , 129 , 131–134 ] with 14,341 hospitalized COVID-19 patients assessed the effect of chloroquine and hydroxychloroquine on length of stay and were included in the meta-analysis. The overall pooled MD was 0.78 (95% CI: -0.34 to 1.89) with significant and severe heterogeneity (I 2 = 91%; p Q <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Hasta la fecha ningún tratamiento propuesto ha sido completamente eficaz para tratar la infección por el SARS-CoV-2. De hecho, miembros de nuestro equipo han determinado que los antivirales de repropósito comúnmente disponibles en México, Cloroquina y Lopinavir, no tienen una actividad considerable en la regulación de esta patología (Sevilla-Castillo et al, 2021), lo cual complica el manejo antiviral, dejándolo relegado al uso de antivirales de baja disponibilidad y alto precio, como son Remdesivir y Bamlanivimab (Frediansyah et al, 2021). Por ello, y dada la Figura 1.…”
Section: Inmunosupresión Vs Inmunorregulación En Covid-19 Immunosuppression Vs Immunoregulation In Covid-19unclassified
“…A retrospective analysis found that both CQ and LPV/RTV showed ineffectiveness in the case of severe COVID-19, whereas a combination of them enhanced mortality [87]. Another cohort study of non-critical COVID-19 patients receiving FPV (n = 154) and triple therapy (INF-beta 1b + RBV + LPV/RTV) showed that the triple therapy decreased mortality [88].…”
Section: Lopinavir-ritonavir (Lpv/rtv)mentioning
confidence: 99%